A first-principles study of electronic, optical and thermoelectric properties of TlXF3 (X: Zn, Sr) perovskite crystal structure. (1st May 2023) - Khan, Sajid; Gassoumi, Abdelaziz; Rahman, Altaf Ur; Ullah, Farhat; Ahmad, Rashid; Mehmood, Nasir; Abdul, M; Shah, Abdul Hakim
Abstract: This study communicates the structural, electronic, optical, and thermoelectric properties of a perovskite TlXF3 (X: Zn, Sr) crystal structure using first-principles calculations. Both compounds were found structurally as well as thermodynamically stable in cubic phase. To check the kinetic stability, the phonon frequancy band structure is calculated which indicates that there is no negative frequency in the phonon spectrum, which confirms the dynamic stability of TlXF3 . The bandgaps of both compounds belong to insulating region. The TlSrF3 exhibits direct bandgap of 4.37 eV at X symmetry point while TlZnF3 possess indirect bandgap of 3.95 eV (M-X). Using HSE functional, the calculated electronic bandgaps of TlSrF3 and TlZnF3 are 5.74 eV(X-X) and 5.36 eV (M-X), respectively. The analysis of electronic states in band structure shows that for TlSrF3, the top of valence band is composed of the F- p states whereas the states in lower potion of conduction band are impacted by the significant contribution of Tl- p orbital states. In case of TlZnF3, the states near the valence band maxima and conduction band minima are coming mainly form Tl atom. The effect of spin–orbit coupling (SOC) on the electronic band structure is also considered. The SOC in the valance band is negligible, while in the conduction band it shows a dominant effect at Γ-point in both TlSrF3 and TlZnF3 compounds. The dependence of thermoelectric properties such as electrical conductivity σ, Seebeck coefficient (S), Power factor (PF), electronic thermal conductivity ( κ ) and figure-of-merit (ZT) as a function of carrier concentration and temperature are investigated. The optical properties were also studied to understand the response of TlXF3 to incident photons of energies upto 14 eV. We conclude that the TlXF3 are promising candidates for electronic, thermoelectric and optoelectronic devices.